“We Vs. They” And The Polarizing Strategy In Bush's West Point Speech (june 1, 2002): The Securitization Of Iraqi Regime - Naime Benmerabet (The Journal of Studies in Language, Culture and Society, 2021)
This article investigates the manipulation of the pronouns “we” and “they” by President Bush in his West Point speech of June 1, 2002. The US president mobilized these pronominal choices to buttress US claims about Iraqi threat and to legitimize US preventive war against Saddam Hussein's regime whose repercussions culminated in the relinquishment of just war rules. The article focuses on disclosing the ideological implications of these choices through the lens of Norman Fairclough’s three-dimensional model of critical discourse analysis. It more specifically elucidates how President Bush harnessed these personal pronouns to re-articulate and co-construct the US identity as being the incarnation of absolute good in contradistinction with the identity of the other (Iraqi regime in this context) which was depicted as being synonymous of absolute evil.